Indo-Pacific empire : China, America and the contest for the world's pivotal region - Medcalf, Rory (Manchester : Manchester University Press, 2020)
The Indo-Pacific is both a place and an idea. It is the region central to global prosperity and security. It is also a metaphor for collective action. If diplomacy fails, it will be the theatre of the first general war since 1945. But if its future can be secured, the Indo-Pacific will flourish as a shared space, the centre of gravity in a connected world. What we call different parts of the world -- Asia, Europe, the Middle East -- seems innocuous. But the name of a region is totemic, guiding the decisions of leaders and the story of international order, war and peace. In recent years, the label'Indo-Pacific' has suddenly gained wide use. But what does it really mean? Written by a globally-renowned expert, Indo-Pacific Empire is the definitive guide to tensions in the area. It deftly weaves together history, geopolitics, cartography, military strategy, economics, games and propaganda to address a vital question: how can China's dominance be prevented without war? -- Dust jacket
Colored maps on end papers.
Includes bibliographical references (pages 273-299) and index.
Keywords: Geopolitics -- Indo-Pacific Region; Indo-Pacific Region -- Foreign relations; Indo-Pacific Region -- Strategic aspects; United States -- Foreign relations -- China; China -- Foreign economic relations -- United States